ACTORS AFFECTING THE OCCURRENCE ASPHYXIA NEWBORN (BBL) IN THE WORK AREA HEALTH SIBREH - Husna, Asmaul (Universitas Ubudiyah Indonesia, 2015)
The infant mortality rate is one indicator in determining thehealth status of children. Every year the death of the newborn or neonatalreached 37% of all deaths in children under five. Every day 8,000 newbornbabies around the world die from causes that can not be prevented. Themajority of all infant deaths, 75% occur in the first weeks of life andbetween 25% and 45% of these deaths occur within the first 24 hours of ababys life. The main causes of neonatal mortality or neonatal worldincluding premature infants born 29%, sepsis and pneumonia 25% and23% of the infants born with asphyxia and trauma, birth asphyxia occupiescause of infant mortality to third in the world in the early period of life(WHO , 2012). Based on the research that has been done so research cansummarize the results of the study as follows There singnifikan effectbetween low birth weight (LBW) with the occurrence of asphyxia innewborns In Puskesmas Sibreh with value p â¤ 0.05 (0.002) There is aneffect singnifikan between maternal age with the onset of asphyxia innewbornsIn Puskesmas Sibreh with value p â¤ 0.05 (0.015) Theresingnifikan influence of gestation with the occurrence of asphyxia innewbornsIn Puskesmas Sibreh with value p â¤ 0.05 (0.022)Keywords: weight, maternal age, gestational age